2013
DOI: 10.7498/aps.62.135204
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on asymmetrical period-one discharge in dielectric barrier discharge in helium at atmospheric pressure

Abstract: Dielectric barrier discharge at atmospheric pressure not only behaves as a symmetrical period-one (SP1) discharge, but can also manifest itself as an asymmetrical period-one (AP1) discharge in certain ranges of parameters. In our study, a parallel electrode configuration is adopted and a series of discharge experiments are carried out in atmospheric helium at gap widths of 1, 4, 7 and 10 mm, respectively. The effects of gap width and driving voltage frequency on the symmetry of period-one discharge are investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In addition, it was revealed by massive reports that before the discharge evolved into chaos and other nonlinear states, it would always firstly bifurcate from typically symmetric singleperiod (SP1) discharge into an asymmetric single-period (AP1) discharge [128][129][130], in which positive and negative pulses differed in shape or magnitude while the period of the current remained the same as that of applied voltage, as shown in figure 37. Therefore, the transition from SP1 to AP1 discharge was regarded as the first step of the bifurcation, or a possible indicator of chaos.…”
Section: Status Of Chaos In Dbdmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was revealed by massive reports that before the discharge evolved into chaos and other nonlinear states, it would always firstly bifurcate from typically symmetric singleperiod (SP1) discharge into an asymmetric single-period (AP1) discharge [128][129][130], in which positive and negative pulses differed in shape or magnitude while the period of the current remained the same as that of applied voltage, as shown in figure 37. Therefore, the transition from SP1 to AP1 discharge was regarded as the first step of the bifurcation, or a possible indicator of chaos.…”
Section: Status Of Chaos In Dbdmentioning
confidence: 99%
“…If the repetitive rate of premature pulses in the temporal profiles altered due to some turbulence, the discharge would transform into multi-periodic states or even chaos. By now, the most commonly accepted explanation for the cause of asymmetric discharge is the effect of residual positive column (generated during the last discharge process) existing at the beginning of a new breakdown process [128,[130][131][132] in that it, for example, increases the non-uniformity of spatial electric field distribution prior to the next discharge, preventing the fully development of the discharge process [129]. It might also act as an equivalent anode that shortened the effective discharge gap, forcing the discharge to operate in an equivalent Townsend mode and initiating a premature current pulse [132].…”
Section: Status Of Chaos In Dbdmentioning
confidence: 99%
“…Recent studies show that the symmetrical discharge in the parallel-plate electrode can become asymmetrical with the increase of the gas 065206-2 gap. [11,[23][24][25] Conversely, the discharge can become symmetrical by reducing the gas gap.…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] These attractive features make them suitable for a broad prospect in industrial and biomedical applications, such as thin film deposition, surface modification, ozone generation, bio-sterilization, and so on. [3][4][5] One of the promising non-equilibrium plasma sources is the dielectric barrier discharge (DBD). Although DBD usually operate in a filamentary form at atmospheric pressure, however, it also can exhibit a homogeneous diffuse mode under certain conditions, which is called the atmospheric pressure glow discharge (APGD).…”
Section: Introductionmentioning
confidence: 99%
“…[13] It is experimentally observed that asymmetric pulsed phenomena were presented in the dielectric barrier glow discharge in helium. [5,14] Ha et al [15] found that the glow mode and the Townsend mode could coexist in the asymmetric discharge. Wang and collaborators [16] demonstrated that a glow discharge can transit into a chaotic mode or a periodic mode with multiple periods by double period bifurcation.…”
Section: Introductionmentioning
confidence: 99%